Comparison of United States and Canadian Glaucoma Medication Costs and Price Change from 2006 to 2013 - Matthew B. Schlenker; Graham E. Trope; Yvonne M. Buys (Journal of Ophthalmology)
Objective. Compare glaucoma medication costs between the United States (USA) and Canada. Methods. We modelled glaucoma brand name and generic medication annual costs in the USA and Canada based on October 2013 Costco prices and previously reported bottle overfill rates, drops per mL, and wastage adjustment. We also calculated real wholesale price changes from 2006 to 2013 based on the Average Wholesale Price (USA) and the Ontario Drug Benefit Price (Canada). Results. US brand name medication costs were on average 4x more than Canadian medication costs (range: 1.9x–6.9x), averaging a cost difference of $859 annually. US generic costs were on average the same as Canadian costs, though variation exists. US brand name wholesale prices increased from 2006 to 2013 more than Canadian prices (US range: 29%–349%; Canadian range: 9%–16%). US generic wholesale prices increased modestly (US range: −23%–58%), and Canadian wholesale prices decreased (Canadian range: −38%–0%). Conclusions. US brand name glaucoma medications are more expensive than Canadian medications, though generic costs are similar (with some variation). The real prices of brand name medications increased more in the USA than in Canada. Generic price changes were more modest, with real prices actually decreasing in Canada.